An evaluation of a target‐controlled infusion of propofol or propofol–alfentanil admixture for sedation in dogs. (April 2016) - Montefiori, F.; Pawson, P.; Auckburally, A.; Scott, M.; Flaherty, D.
Abstract : OBJECTIVES: To evaluate sedation quality and cardiorespiratory variables in dogs sedated using a target‐controlled infusion of propofol or propofol–alfentanil admixture. METHODS: A total of 60 dogs undergoing diagnostic imaging were randomly assigned to one of three sedation protocols: propofol alone; propofol with a low concentration of 12 µg of alfentanil per mL of propofol; or propofol with a higher concentration of 24 µg of alfentanil per mL of propofol. Target‐controlled infusion was initiated at a propofol target concentration of 1·5 µg/mL and increased until lateral recumbency was achieved. Times to adopt lateral recumbency and recover, pulse rate, respiratory rate, oscillometric mean arterial pressure and oxygen saturation were recorded. Quality of sedation onset and recovery were scored. RESULTS: Propofol target at lateral recumbency differed significantly (P=0·01) between groups with median (range) values of 3·0 (1·5 to 5·5), 2·0 (2 to 4·5) and 2·25 (1·5 to 3·5) µg/mL for propofol alone, propofol with the lower concentration of alfentanil and propofol with the higher concentration of alfentanil groups, respectively. Time to lateral recumbency was longer and quality of onset less smooth for the propofol group. Pulse rate change differed significantly (P<0·001) between groups (mean pulse rate change at onset of sedation: propofol group +2 ±24 bpm, low concentration alfentanil group −30 ±24 bpm, higher concentration alfentanil group −26 ±23 bpm). Hypoxaemia (SpO2 <90%) occurred in 1, 3 and 13 dogs, in the propofol group, the low concentration alfentanil group and the higher concentration of alfentanil group, respectively (P<0·001). CLINICAL SIGNIFICANCE: Addition of alfentanil to propofol target‐controlled infusion did not confer cardiovascular benefits and, at the higher concentration, alfentanil increased the incidence of hypoxaemia.